Creole Jesuits in the Province of New Spain in 1767 : Architecture, Organization, Profile, and Identity - Jackson, Robert H., (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
In 1767, King Carlos III of Spain ordered the expulsion of the Jesuits from his dominions. This study examines the Jesuits in the Province of New Spain (Mexico, Cuba, Guatemala) at the time of the expulsion, their urban educational and spiritual role, and their administration of frontier missions. The King sent the exiled Jesuits to live out their lives in the Papal States. The book also explores the profile (i.e. the collective biography) of the Jesuits, and their fate following the expulsion. At the time of the expulsion, the majority of the Jesuits in New Spain were born in the Americas, mostly in Mexico. The Jesuits invested large sums of money in the construction of urban colegios, which are here analyzed together with the rest of the Jesuit architectural patrimony.